Delegacy visit report: UIN Sunan Kalijaga to Academy of Contemporary Islamic Studies, UiTM Pulau Pinang Branch / Hisyam Mohd Radzi … [et al.] - Mohd Radzi, Hisyam; Ayob, Habibah; Ahmad, Nurfahiratul Azlina; Dahalan, Zulkifli; Ab Lateh, Ahmad Temizi (UiTM Global @ Office of International Affairs, 2024)
On 24 October 2023, a significant delegation visit took place between UIN Sunan Kalijaga from Indonesia and the Academy of Contemporary Islamic Studies (ACIS) at Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia. The purpose of this visit was to foster academic collaboration, exchange knowledge, and explore shared interests in the realms of maqasid syariah, halal tourism, and science and technology.